2018
DOI: 10.1111/mcn.12674
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of commercial infant products and fortified staple foods to nutrient intake at ages 6, 12, and 18 months in a cohort of children from a low socio‐economic community in South Africa

Abstract: Fortification of two staple foods, maize meal and wheat flour (bread), is mandatory, and commercial infant products are widely available in South Africa. Using a 24-hr recall, we determined the contribution of these foods towards nutrient intakes at ages 6 (n = 715), 12 (n = 446), and 18 (n = 213) months in a cohort of children in a peri-urban community, North West province. On the day of recall, commercial infant products were consumed by 83% of children at 6 months, 46% at 12 months, and 15% at 18 months; fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
5
24
1
Order By: Relevance
“…Nutrients derived from consuming the optimal bean‐based snack were computed from the nutrient density per 100 kcal and direct comparison with the recommended daily intake (RDI) for children aged 4–12 years (Swanepoel et al., 2018). Estimation of the nutrient density and nutrient contribution showed that from 100 g snack serving of the optimal extruded bean snack if consumed would provide at least 60%, 48%, or 19% of the RDI for protein, iron, and zinc, respectively, for 9‐ to 12‐year‐old and more than 100% for 4–8 year children (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrients derived from consuming the optimal bean‐based snack were computed from the nutrient density per 100 kcal and direct comparison with the recommended daily intake (RDI) for children aged 4–12 years (Swanepoel et al., 2018). Estimation of the nutrient density and nutrient contribution showed that from 100 g snack serving of the optimal extruded bean snack if consumed would provide at least 60%, 48%, or 19% of the RDI for protein, iron, and zinc, respectively, for 9‐ to 12‐year‐old and more than 100% for 4–8 year children (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…In Study 1 , additional data were collected 6 months after the completion of the RCT (at age 18–24 months). In Study 3 (Smuts et al ; Swanepoel et al, ), dietary intake data were collected for children who participated in an RCT that was done in a peri‐urban site in North West province. Study participants were recruited through primary health care facilities and house‐to‐house visits.…”
Section: Methodsmentioning
confidence: 99%
“…In vulnerable populations in South Africa, dietary intake in 6–24‐month‐old children can range from predominantly maize‐based to predominantly based on commercial infant foods (Faber, ; Faber, Laubscher, & Berti, ; Swanepoel et al, ). Pooling diverse dietary intake data would potentially provide a dataset with sufficient variation to determine the nutrient profile of a variety of dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Infant cereals play an important role in complementary feeding in both developed and low-income countries [ 16 , 17 , 18 , 19 , 20 ]. Infant cereals enhance nutritional intake, compensate iron depletion at the beginning of complementary feeding, foster the development of microbiota and are suitable for a transition from milk to solid foods due to the mild taste and semi-solid texture [ 11 ].…”
Section: Introductionmentioning
confidence: 99%